THE IMAGE OF WOMEN AND THEIR ROLE IN SOCIETY IN THE WORKS OF JADIDS - Arapjonova Zebo Otabek qizi (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This article explores the portrayal of women and their societal roles in the literary  and  cultural  works  of  the Jadid  movement. The  Jadids, as  reformist intellectuals of the late 19th and early 20th centuries in Central Asia, advocated for modernization, education, and social reforms, including the advancement of women's status.  Through  analysis  of  key  texts  and  writings,  this  paper  examines  how  Jadid authors  depicted  women  as  crucial  agents  of  cultural  renewal  and  social  progress, emphasizing their education, emancipation, and moral influence within the family and society. The study highlights the complex and sometimes ambivalent perspectives on gender roles, reflecting both traditional values and progressive ideas characteristic of the Jadid reform agenda.